Integração corporativa e engenharia simultânea: estratégias para desenvolvimento e gerenciamento de projetos: estudo de caso em indústria multinacional agrícola - Schmitt, Sidnei Vinicius (Universidade do Vale do Rio dos Sinos, 2020)
The integration of companies strategic plans goes through the operational, strategic and departmental specific tactics levels, with the objective of optimizing and systematizing productivity gains and taking advantage of the stages of each project. It is understood that such internal processes can generate competitive advantages through the integration of initial marketing plans and company objectives with project management. Given the major difficulties encountered in managing a project, as well as the great interest of companies in optimizing the flow of information and integration of internal processes, this paper aims to present two main ways to solve integration problems and to increasing business productivity: knowledge integration and concurrent engineering. The methodology will be based on bibliographic research, case study and action research. Will have a qualitative approach in the analysis of project information and structure of each department, in order to understand the behavior and results of each sector involved, during each step of the process; as well as a quantitative approach in obtaining the data and information necessary for failure and opportunity analysis.
Keywords: Planejamento estratégico; Integração de conhecimento; Engenharia simultânea; Identificação de oportunidades; Strategic planning; Knowledge integration; Concurrent engineering; Opportunity identification; ACCNPQ::Ciências Sociais Aplicadas::Administração